Are ecological modernization narratives useful for understanding and steering social - ecological change in the Argentine Chaco? - Mastrángelo, Matías (2019)
Fil: Mastrángelo, Matías. Universidad Nacional de Mar del Plata. Facultad de Ciencias Agrarias. Grupo de Estudio de Agroecosistemas y Paisajes Rurales (GEAP). Mar del Plata, Buenos Aires, Argentina.